The Rate of Fast-Food Consumption among Teenagers in Derna City Libya - Hamd Younis, Fareha; Eljamay, Salwa; Eldali, Amna Mansour (Al-Mukhtar Journal of Sciences, 2020)
The purpose of this study is to find out about the fast-food consumption of adolescents between the ages of 13-25 years old in Derna city and its effect on health. The samples included 100 adolescents from both sexes, a descriptive cross-sectional study of teenagers was conducted. The questionnaire was divided into two parts: the first part was related to socio-demographic information and part two to junk food patterns and inﬂuencing factors of junk food consumption. A value of P < 0.05 was interpreted as statistically significant. The findings revealed that more girls (67.0%) consumed fast food than boys, and approximately half (49.0%) of participants were consuming fast food as an alternative to the main meal, and more than half of participants (63.0%) were consuming soft drinks every day. The results concludes that adolescents consumed a greater amount of junk food, which subsequently led to a majority of ill effects.